Administrative Ethics in Noordin Hassan's Sirih Bertepuk Pinang Menari and Mana Setangginya? (Etika Pentadbiran dalam Sirih Bertepuk Pinang Menari dan Mana Setangginya? Noordin Hassan) (Malay Literature, 2015)
Sasterawan Negara Dato' (Dr.) Noordin Hassan's apprehension about the abuse of power can be seen in all his plays and noticeably so in his plays Sirih Bertepuk Pinang Menari (1992) and Mana Setangginya? (1999). While Sirih Bertepuk Pinang Menari is more Malay, Mana Setangginya? has a more global and universal message. The first layer of Noordin's plays will offer a chance to look for the main message of the play or to find significance in the main storyline or in other devices. As Noordin says in Sirih Bertepuk Pinang Menari, "If what is stated is impossible, then one should search for what is hidden". The administrative ethics that Noordin propagates is the "hidden" and major statement behind the comedy, romance and splendour of both plays.Keywords: administrative ethics, governance, Noordin Hassan, hidden